Rancang Bangun E-LKPD Berbasis Problem Based Learning Terintegrasi Nilai Tri Kaya Parisudha Pada Jenjang Sekolah Dasar - Putu Triska Prateja; Ni Nyoman Kurnia Wati; Ni Putu Candra Prastya Dewi (Cetta: Jurnal Ilmu Pendidikan, 2026)
Learning motivation and cognitive achievement among Grade IV IPAS students at SD N 3 Kayuputih Melaka have declined, characterized by teacher-centered instruction, a lack of local culture based digital teaching materials, and a downward trend in formative scores with the average dropping from 77.2 to 69.3 and the proportion of students scoring below the minimum mastery threshold (KKTP) surging from 30% to 55%. This study aimed to design, develop, and evaluate an electronic student worksheet (E-LKPD) based on Problem Based Learning (PBL) and infused with Tri Kaya Parisudha (TKP) values ​​for Grade IV IPAS instruction. The study employed a Research and Development (R&D) approach using the ADDIE model, involving three expert validators, one teacher, six students in a small-group trial, and thirty students in a field trial; data were analyzed using descriptive statistics, the normalized N-Gain index, and a paired t-test. Validation results showed an average score of 89.45% (categorized as "highly valid"), covering three dimensions: content-pedagogical depth (90.63%), media-interface quality (90.22%), and linguistic readability (87.50%). Practicality achieved an average of 94.54% (categorized as "highly practical"), with consistent results across teacher feedback (95.00%), the small-group trial (95.83%), and the field trial (92.78%). Regarding effectiveness, the average pre-test score of 52.17 rose to 86.33 in the post-test, yielding a normalized N-Gain index of 0.71 (high category); 60% of students fell into the high category and 40% into the medium category, with none in the low category; classical mastery reached 93.33%, exceeding the 80% threshold; and the paired t-test yielded t(29) = 24.37 (p < 0.001) with a Cohen’s d of 3.63, indicating a very large effect size. The PBL-based E-LKPD incorporating *Tri Kaya Parisudha (TKP) values ​​has been proven valid, practical, and effective in improving learning outcomes in Natural and Social Sciences (IPAS) for fourth-grade elementary students, and is worthy of recommendation as an innovative teaching material for primary schools with similar characteristics.